Tecnologia educacional como facilitadora do raciocínio diagnóstico do enfermeiro no cuidado ao paciente cirúrgico - Paschoal, Jociani Gonçalves (2019)
Introduction: The post-surgical patient presents several physiological changes. The Nursing Process allows for the care to be done in a systematic and qualified manner. The difficulties in the development of Diagnostic Reasoning, and the deficit in the knowledge about the classifications have instigated the undertaking of this research. Hence, seeking to meet the demand of the institution, the creation of an application, since the educational technologies help in the professional updating, and technologies such as mobile applications motivate learning, for their audio-visual resources and easy access. This project is in line with the line of research on nursing care in the human development process, and seeks to meet the demand for permanent education through the professional updating of nurses working in the general surgery unit and academics of the institution. Objective: To develop an application to support the diagnostic reasoning of the Nurse in the care of the surgical patient. Methodology: It is an applied research of technological production developed in four stages.1) Preparation of theoretical material for Nursing Assistance to surgical patients through literature integrative review and cross-mapping. 2) Development of study cases. 3) Study cases evaluation. 4) Mobile application building. Results: In the literature integrative review, 32 studies were selected, and 49 signs and symptoms were found. The cross-mapping between the signs and the symptoms with the Nursing Diagnostic Taxonomy North American Nursing Diagnoses Association International identified 61 Nursing diagnoses. The study of cases were built according to the 8 Lunney’s presuppositions, addressing the main types of surgeries done in the sector of study, and the main Nursing diagnoses found in the cross-mapping. In addition of the objective and subjective data related to the simulated patients, the case studies have multiple choice alternatives for the resolution of the main Nursing diagnosis. The 10 case studies were evaluated by 15 judges, and they all obtained a global content validity index higher than 0.8. The application “CuidarTech Cirúrgico” presents, on its main menu, four navigation options. “Nursing Process” exhibits theoretical content about the Nursing Process, the Basic Human Needs Theory, North American Nursing Diagnoses Association International, Nursing Interventions Classification, Nursing Outcomes Classification, and International Classification of Nursing Practice. “Nursing Diagnosis and Interventions” contains 61 diagnosis, 388 interventions and Nursing activities that are important for the assistance of patients in the post-surgical period of gastric-intestinal, thoracic and neck surgery. “Study Cases” brings the 10 study cases developed and evaluated for the training of the clinical reasoning and diagnosis. When the user chooses incorrect alternatives, the user then has access to the information about the signs and symptoms that support the correct diagnosis. And when the right diagnosis is chosen, the user then has access to the signalled diagnosis, and to which are the defining characteristics that deny wrong diagnosis. “Credits” has information about the team responsible for the creation of the application. Conclusion: Educational technologies, such as the application created, are efficient strategies for the teaching of the Nursing Process, support the diagnostic reasoning, and decision making. This research has the potential to generate impact and be applied at local, regional and national levels. The application will benefit undergraduate students indirectly, especially those who take practical classes, curricular and extracurricular internships, and in other scenarios where the educational technology might be divulged. The social impacts may be professional qualification, improvement in the quality of the Nursing assistance, patient safety, improvement in the undergraduate teaching, and the consolidation of the Nursing Process. Dissertation presented at the meeting of the “Professional Master Cofen-CAPES” at the 22nd Brazilian Congress of Nursing Councils, held in Foz do Iguaçu-Paraná.